(untitled) (Proceedings of International Educators Conference, 2024)
Modern management of companies operating in the conditions of market economy, enterprises, their embodied as a system of production and economic activity of the organizations and management necessary to maintain the effective functioning and development that will create the conditions holds. Of Mediamenegmant by the author of the article the essence, is the study of the basic concept and its specific features. Mediamanagement in organizational structure and to study the effects of its business activities on the outcome of the developments outlined copyright and they stuck. Media managerning functions, causing their professional and personal competence mentioned.